2019
DOI: 10.3389/fnmol.2019.00094
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid System in Spinocerebellar Ataxia Type-3 and Other Autosomal-Dominant Cerebellar Ataxias: Potential Role in Pathogenesis and Expected Relevance as Neuroprotective Targets

Abstract: Spinocerebellar ataxias (SCAs) are a group of hereditary and progressive neurological disorders characterized by a loss of balance and motor coordination typically associated with cerebellar atrophy. The most prevalent SCA types are all polyQ disorders like Huntington’s disease, sharing the most relevant events in pathogenesis with this basal ganglia disorder, but with most of the damage concentrated in cerebellar neurons, and in their afferent and efferent connections (e.g., brainstem nuclei). SCAs have no cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…On the other hand, some older studies indicate that enhancing CB1-dependent signaling may affect in ataxic symptoms [185,186]. CB2 activation is proposed for neuroprotection [187].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…On the other hand, some older studies indicate that enhancing CB1-dependent signaling may affect in ataxic symptoms [185,186]. CB2 activation is proposed for neuroprotection [187].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…The upregulation of CBRs in the CNS has been detected in epilepsy and numerous neurodegenerative diseases, possibly leading to protect neurons from excitotoxicity (Pacher et al., 2006). A more recent pathological study on the cerebellum reported that post‐mortem tissues from patients with type 3 of spinocerebellar ataxia (SCA‐3) had elevated expression levels of CB 1 Rs and CB 2 Rs in PCs (Gómez‐Ruiz et al., 2019; Rodríguez‐Cueto et al., 2014). This upregulation is also although to contribute to the inhibition of neuronal excitation, thus protecting PCs from neurodegeneration in the SCA‐3 cerebellum (Gómez‐Ruiz et al., 2019; Rodríguez‐Cueto et al., 2014; Stephens, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A more recent pathological study on the cerebellum reported that post‐mortem tissues from patients with type 3 of spinocerebellar ataxia (SCA‐3) had elevated expression levels of CB 1 Rs and CB 2 Rs in PCs (Gómez‐Ruiz et al., 2019; Rodríguez‐Cueto et al., 2014). This upregulation is also although to contribute to the inhibition of neuronal excitation, thus protecting PCs from neurodegeneration in the SCA‐3 cerebellum (Gómez‐Ruiz et al., 2019; Rodríguez‐Cueto et al., 2014; Stephens, 2016). Alternatively, the upregulation may disturb PC output signals, and perturb accurate signal transmission at synapses between PCs and their target neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both natural and synthetic cannabinoids are neuroprotective after various types of CNS insults, such as stroke [ 103 ]. Preclinical models show activation of CBRs can trigger removal of activated immune cells [ 75 ], downregulate pro-inflammatory cytokine and chemokine production [ 104 ], and inhibit HIV-associated synapse loss and neural injury [ 105 ]. In vitro, THC treatment suppresses several pro-inflammatory factors, including TNF-α, IL-6, and IL-8, and decreases monocyte-derived interleukin IL-1ß production and astrocyte secretion of MCP-1 and IL-6 from a human coculture system [ 106 ].…”
Section: Cannabinoids and Inflammation In The Brain In Hivmentioning
confidence: 99%